Conflitos ambientais em Minas Gerais: exploração da água na microrregião de São Lourenço - Eder Jurandir Carneiro; Mauro Francisco da Costa Assis (Estudios Sociales)
The research aims to identify and to analyze the cases of environmental conflicts involving dissimilarities of power in the determination of the use of territories and its natural resources in the microregion of São Lourenço (Minas Gerais, Brazil). For this data surveys were conducted in the archives of the Ministério Público do Estado de Minas Gerais (MPMP), as well in interviews and workshop with social movements engaged in struggles for environmental justice in the middleregion south-southwest of Minas Gerais where is located the microregion of São Lourenço. The findings data show that the MPMP focus its attention on the investigation and punishment of small violations of environmental legislation. The article analyze specifically at the case of environmental conflict related to the fight against the exploitation of groundwater in the city of São Lourenço. The study adopts the theoretical framework based upon the concept of environmental conflicts, pointing out the conflictive nature of environmental issues, from the recognition that society and the environment are inseparable, because the material world is cut by subjects that build different projects of use and meaning of space and natural conditions.